Expanded subsurface ocean anoxia in the Atlantic during the Paleocene-Eocene Thermal Maximum - Weiqi Yao; Tianshu Kong; Xingchen Tony Wang; Ruixiang Zhai; Ruiling Zhang; Yilin Liu (Nature Communications, 2024)
Abstract The ocean has experienced substantial oxygen loss over recent decades, affecting marine ecosystems and fisheries. Investigating ocean deoxygenation during hyperthermal events, such as the Paleocene-Eocene Thermal Maximum (PETM), offers insights into its future dynamics. Here, sediment cores from the South Atlantic reveal a pronounced decline in foraminifera-bound δ15N, concurrent with an increase in marine barite δ34S and enhanced ocean productivity during the PETM. These findings suggest an expansion of oxygen-deficient zones (ODZs) from suboxia to anoxia in the thermocline, with ammonium and sulfide accumulation. Model simulations indicate “ammonium-type” ODZs were driven by Southern Ocean warming and elevated productivity. Intense fixed nitrogen loss at the upper boundary of these ODZs, along with increased oceanic phosphorus inventory, likely spurred a compensatory rise in N2 fixation. While the Pacific might experience different oxygenation conditions during the PETM, parts of the Atlantic thermocline became anoxic, highlighting potential spatial variabilities of ocean deoxygenation under global warming.